2015
DOI: 10.1093/humrep/deu352
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identified new susceptibility loci for polycystic ovary syndrome

Abstract: This work was supported in part by the grant from the Korea Centers for Disease Control and Prevention (2009-E00591-00). The work was also supported by the Ewha Global Top5 Grant 2013 of Ewha Womans University. None of the authors has any conflict of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 48 publications
0
71
2
2
Order By: Relevance
“…Hyperandrogenism likely drives acne in PCOS, although as it is a proinflammatory disease, immune genes and cytokines could likewise predispose to acne symptoms (Table ) . A number of GWASs have been performed for PCOS . Hormonal therapies are a well‐tolerated and effective way to control acne with and without endocrine disorders .…”
Section: Human Disorders That Cause Acne‐like Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperandrogenism likely drives acne in PCOS, although as it is a proinflammatory disease, immune genes and cytokines could likewise predispose to acne symptoms (Table ) . A number of GWASs have been performed for PCOS . Hormonal therapies are a well‐tolerated and effective way to control acne with and without endocrine disorders .…”
Section: Human Disorders That Cause Acne‐like Phenotypesmentioning
confidence: 99%
“…[129][130][131][132][133] A number of GWASs have been performed for PCOS. [134][135][136][137][138] Hormonal therapies are a well-tolerated and effective way to control acne with and without endocrine disorders. 139,140 CAH is linked to endocrine abnormalities with deficiency in the synthesis of cortisol from the adrenal cortex.…”
Section: Endocrine System Syndromesmentioning
confidence: 99%
“…In recent years, genomewide association studies have been used to identify susceptibility loci for PCOS . Research on variation in telomere lengths in the human genome has gradually expanded into the field of reproduction, and studies have also reported associations between telomere length and PCOS .…”
Section: Introductionmentioning
confidence: 99%
“…None of the selected gene variants had been reported to have an association with PCOS. However, rs1159315 found from GWAS with PCOS has shown a positive association with PCOS development in Korean women (4p12, p overall = 1.43 × 10 -5 ) in Lee et al [39]. The SNP is located near genes including gamma-aminobutyric acid A receptor, alpha 4 (GABRA4), gamma-aminobutyric acid A receptor, beta1 (GABRB1), cytochrome c oxidase subunit VIIb2 (COX7B2) and copper metabolism murr1 domain-containing 8 (COMMD8).…”
Section: Discussionmentioning
confidence: 93%